PENERAPAN MEDIA SEJARAH LOKAL NILAI FILOSOFIS BANGUNAN RUMAH KAMPUNG ARAB 13 ULU DI SMA YWKA PALEMBANG - Dewi Setyawati; Fatmah Fatmah; Nurhayati Nurhayati; Yusinta Tia Rusdiana; Dewi Purnama Sari (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The reason for carrying out this community service is the low interest of students in learning history. The low learning motivation of students, especially in learning local history, results in students being lazy to study history. Then, there is a lack of media based on local history created by History Teachers. It also strengthens students' character through media through a banner on the philosophical values ​​of the Arab Village House Building 13 Ulu Palembang at YWKA Palembang High School. The methods used in this community service activity are first, making initial preparations starting from administration; secondly, carrying out material presentations or explanations according to the material and providing available Media Banners; and thirdly, carrying out intensive reviews with understanding to all participants. Then, evaluate the activity from start to finish by ensuring all participants can understand what was conveyed to the presenter until its implementation. It is hoped that by donating this banner material and media, History Teachers at YWKA Palembang High School can apply it to students at the school to increase interest in learning local history and strengthen the students' character.